Pictorial prescribing reduces error in administration of fentanyl for breakthrough pain. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Booth, Stephen; Gloag, Maria; Kinna, Sara; Wheble, Andrew Bell Jo; Wheeler, Daniel
Abstract : Objectives: Fentanyl is commonly used in patients with transient exacerbations of cancer pain due to its rapid transmucosal absorption. Intranasal sprays, sublingual tablets, and buccal tablets or lozenges are available. The preparations are not interchangeable, with varying bioavailability, creating potential for opioid prescribing errors. This study aimed to demonstrate a reduction in opioid medication errors via a novel and low cost strategy: the use of printed stickers for prescription charts with a pictorial cue illustrating the preparation. Methods: Fifty-four nurses from our institution were shown 10 handwritten or printed pictorial sticker prescriptions for fentanyl for breakthrough pain. They were asked to indicate which preparation and dose they would administer from boxes of Instanyl (Nycomed), Abstral (ProStrakan), Effentora and Actiq (Cephalon), and to indicate the ease with which they understood the prescription on four-point Likert items. The authors measured the frequency with which nurses selected the wrong preparation or dose. Likert items were analysed categorically as positive or negative responses. Results are reported as OR with 95% CI, and were compared using the χ 2 test. Results: Nurses were more likely to choose the correct fentanyl preparation when using pictorial printed stickers compared to handwritten prescriptions: errors were significantly reduced from 20 to 6 (OR 3.52, 95% CI 1.39 to 8.90, p<0.005). Also, dose errors were non-significantly reduced from 27 to 19 (OR 1.47, 95% CI 0.80 to 2.70, p=0.057). Analysis of Likert items showed a significant improvement in understanding of which preparation to administer: positive responses increased from 227 of 267 responses with handwritten prescriptions to 247 of 266 responses with pictorial printed stickers (p<0.0005). Conclusion: Using pictorial printed stickers is an effective strategy for reducing errors in choice of rapid-onset fentanyl preparations. There may be a wider use for pictorial prescribing where many non-interchangeable preparations of the same drug exist.